Inter-professional prescription safety workshop for non-medical prescribing and pharmacy students: A cross-sectional study - Steve Hemingway; Margaret Culshaw; John Stephenson (British Journal of Pharmacy, 2019)
This article reports on an evaluation of a prescribing workshop to increase ‘shared learning’ between registered practitioners undertaking a non-medical prescribing (NMP) course (midwifery, nursing, physiotherapy, and podiatry) and undergraduate pharmacy students to increase awareness of, and understanding of the roles. The focus was on three domains of safe prescribing: Knowledge (of commonly prescribed medicines and their suitability for individual patients); Process (of legal requirements and supply of medicines and associated patient information); and Relationships (between prescribers and pharmacists). A cross-sectional evaluation was utilized with6-point Likert-style items and a free text section, completed by 337participants. Participants reported positively about the workshop content and their learning experience, although some differences between pharmacy and NMP participants were noted in the knowledge domain. Quantitative analysis revealed significant differences (p<0.001) of low-to-moderate magnitude (partial-2=0.146) between NMP and Pharmacy student on all 3 domains, with NMP students reporting slightly more positive outcomes(between 0.4 and 1.5 points higher) in all cases. However, both groups scored positively; with mean domain scores of 15.6 to 16.5 on scales with maximum scores of 18.